Design and analysis of a displacement sensor-integrated compliant microgripper based on parallel structure - Ho, Nhat Linh; Dang, Minh Phung; Dao, Thanh-Phong (Vietnam Journal of Mechanics, 2020)
This study evaluates the displacement sensitivity of a new compliant microgripper. The microgripper is designed based on a four-bar mechanism and the concept of a compliant mechanism. The effects of the width of the right circular hinge, the thickness of microgripper, and the material properties on the dis-placement sensitivity are considered via using the finite element method. In the beginning, the stress and deformation of the compliant microgripper are evaluated. Subsequently, the displacement of the microgripper is then analyzed. The results showed that the design parameter and the displacement sensitivity have a close relationship. To increase the grasping reliability and measure the displacement or force, a micro-displacement sensor is integrated with the proposed microgripper. Finally, the modeling and analysis of the proposed sensor are conducted.